Implementasi Modul Berbasis Socio-Scientific Issues (MOSSI) pada Materi Pencemaran Lingkungan untuk Meningkatkan Literasi Sains Siswa - Ismah, Ismah; Haryadi, Rudi; Antarnusa, Ganesha (Jurnal Ilmiah Wahana Pendidikan, 2024)
The background behind this research is the low level of science literacy of Indonesian students, as shown by the PISA 2022 results. Environmental pollution is a socio-scientific phenomenon that often occurs and has not been resolved. Socio-scientific issue-based learning about environmental pollution can help students understand the environment and find scientific solutions to overcome these challenges. Creating a socio-scientific issues-based module on environmental pollution is one of the efforts to improve science literacy. The purpose of this research is to develop a socio-scientific issues-based module that can improve students' science literacy. The research method used was the research and development (R&D) method with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). A total of 34 Olympic X-class students were selected as research subjects through the application of the purposive sampling technique. The data collection instruments used were expert validation sheets, student response questionnaires, and science literacy tests (pre-test and post-test). Likert scale and n-gain analysis were used as data analysis techniques. Material and media experts assessed the feasibility of the module and gave an assessment of 83.21% and 86%, respectively, with a very valid category. The student response score of 82.63% was included in the very good category. The results of the trial use of the module on students give an n-gain value of 0.44 with a moderate improvement category. Thus, the socio-scientific issues-based module developed can improve students' science literacy.